Engineering Metamaterials - Maslovski, Stanislav (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
A couple of decades have passed since the advent of electromagnetic metamaterials. Although the research on artificial microwave materials dates back to the middle of the 20th century, the most prominent development in the electromagnetics of artificial media has happened in the new millennium. In the last decade, the electromagnetics of one-, two-, and three-dimensional metamaterials acquired robust characterization and design tools. Novel fabrication techniques have been developed. Many exotic effects involving metamaterials and metasurfaces, which initially belonged in a scientist's lab, are now well understood by practicing engineers. Therefore, it is the right time for the metamaterial concepts to become a designer's tools of choice in the landscape of electronics, microwaves, and photonics. Answering such a demand, the book "Engineering Metamaterials" focuses on the theory and applications of electromagnetic metamaterials, metasurfaces, and metamaterial transmission lines as the building blocks of present-day and future electronic, photonic, and microwave devices.